Istota przyrzeczenia - Gardies, Jean-Louis (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1995)
According to the author the nature of promise presents a twofold problem. First refers to the question why and how an utterance may cause action; second – to the question why and how this action may cause a duteous state, or action. The conclusions drawn from these analyses can facilitate legal statements concerning the nature of promise.